2001
DOI: 10.1177/009207030102900102
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction: A Meta-Analysis of the Empirical Evidence

Abstract: The growing number of academic studies on customer satisfaction and the mixed findings they report complicate efforts among managers and academics to identify the antecedents to, and outcomes of, businesses having more-versus less-satisfied customers. These mixed findings and the growing emphasis by managers on having satisfied customers point to the value of empirically synthesizing the evidence on customer satisfaction to assess current knowledge. To this end, the authors conduct a meta-analysis of the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
237
1
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(301 citation statements)
references
References 0 publications
20
237
1
16
Order By: Relevance
“…Research has shown that equity is related to satisfaction (Szymanski and Henard, 2001), particularly in terms of (un)fair pricing (Oliver and Shor, 2003). Customer satisfaction has been defined as a post-consumption evaluation (Szymanski and Henard, 2001) which results from a comparison of previously held expectations with the perceived product. Hence, consumers' price perceptions are considered an important factor which influences overall satisfaction judgments (Herrmann et al, 2007).…”
Section: Outcomes Of Unfairness Perceptionmentioning
confidence: 99%
“…Research has shown that equity is related to satisfaction (Szymanski and Henard, 2001), particularly in terms of (un)fair pricing (Oliver and Shor, 2003). Customer satisfaction has been defined as a post-consumption evaluation (Szymanski and Henard, 2001) which results from a comparison of previously held expectations with the perceived product. Hence, consumers' price perceptions are considered an important factor which influences overall satisfaction judgments (Herrmann et al, 2007).…”
Section: Outcomes Of Unfairness Perceptionmentioning
confidence: 99%
“…Following self-perception theory, if a consumer discloses feelings and opinions publicly he/she will feel socially committed to adhere to this position (Szymanski & Henard, 2001).…”
Section: The Influence Of Negative O-wom On Repatronage and Switchingmentioning
confidence: 99%
“…Thus, there exists sufficient literature that considers perceived value as an antecedent of satisfaction (Anderson, Fornell, & Lehmann, 1994;Durvasula, Lysonski, Mehta, & Peng, 2004;McDougall & Levesque, 2000;Oh, 1999;Patterson & Spreng, 1997;Ravald & Grönroos, 1996;Singh & Sirdeshmukh, 2000;Spreng, Dixon, & Olhavsky, 1993;Szymanski & Henard, 2001;Woodall, 2003) and this relationship has also been found specifically in tourism. In package tourism Lee, Yoon, and Lee (2007) observe that this relationship occurs in every dimension of perceived value.…”
Section: Perceived Value To Tourism Destinationmentioning
confidence: 99%